Relevansi Maqashidu Shariah dan Kompilasi Hukum Islam Dalam Pandangan Pernikahan Wanita Hamil di Luar Nikah - Khalim, Ahmad Dwi Nur; Chailani, Muchammad Iqbal; Solakhudin, Solakhudin (Universitas Muhammadiyah Metro, 2024)
This study aims to analyze the relevance between Maqashid Shariah and the Compilation of Islamic Law (KHI) in the view of marriage of pregnant women out of wedlock. The phenomenon of pregnancy out of wedlock, which is often a controversial topic in society, is researched through the analysis of Islamic law and its implementation in the context of Indonesia. Using the literature method, this study examines literature related to Islamic marriage law, Maqashid Shariah, and the Compilation of Islamic Law (KHI). This analysis finds that although there are differences of opinion among scholars regarding the ability of pregnant women to marry outside of marriage, the principles of Maqashid Shariah, such as hifzh al-irdh (safeguarding honor), provide a strong basis for considering such abilities for the sake of benefit and justice. In addition, the study of KHI shows that there are stricter rules compared to the views of classical scholars, which need to be reviewed in the context of the needs of modern society. These findings indicate the importance of integrating Maqashid Shariah principles in the implementation of contemporary Islamic law to achieve justice and the welfare of the ummah